ANDROID-BASED HANDOUT DEVELOPMENT TRAINING AS A DISTANCE LEARNING MEDIA FOR SCIENCE AND IPS TEACHERS OF SMP MUHAMMADIYAH 1 PADANG - Zikra Zikra; Febri Yanti (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2022)
The purpose of this service activity is assistance in the development of android-based handouts that are in accordance with the subjects taught by the teacher. This service team is a lecturer who teaches and is an expert in the fields of learning media, strategies and learning design. This is very helpful in solving partner problems. In addition, one of the research results of the service team in the form of learning media design contributes to choosing the right learning media for distance learning. Therefore, the training material includes two things, namely 1) getting to know handouts and the SAC application, 2) making android-based handouts using the SAC application. The method used in this activity is the lecture method, and demonstration or joint practice in making android-based handouts using SAC application that will be carried out by a team of lecturers at partner locations.